SINTESIS MEMBRAN AKRILONITRIL BUTADIENA STIRENA TERMODIFIKASI FILLER SULFONASI GRAFENA OKSIDA TEREDUKSI DAN CERIUM OKSIDA - Riska Listiarini Iskandar; Sarah Dampang; Muhammad Fahmi Hakim; Meka Saima Perdani; Firgi Siswantito; Eri Widianto; Najmudin Fauji (Fakultas Teknik Universitas Wahid Hasyim, 2025)
The utilization of Acrylonitrile Butadiene Styrene (ABS) polymer as an alternative membrane for Direct Methanol Fuel Cell (DMFC) applications has been investigated. This study aims to evaluate the effect of sulfonation temperature on the performance of ABS membranes modified with reduced graphene oxide/cerium oxide (s-rGO/CeO₂). The membranes were synthesized via sulfonation at 65 °C, 75 °C, and 85 °C, with a filler composition of 3% v/v. The results indicate that the addition of filler significantly increases the Ion Exchange Capacity (IEC), with the highest value of 0.375 meq/g obtained at a sulfonation temperature of 85 °C, while methanol permeability was optimally reduced at 65 °C (1.26684 × 10⁻⁷ cm²/s). FTIR analysis confirms successful sulfonation, as evidenced by the appearance of sulfonate (S=O) absorption peaks at 1054 cm⁻¹ and carbonyl (C=O) peaks at 1734 cm⁻¹, indicating interactions between the filler and the ABS matrix. The increased polarity and hydrophilicity of the membrane resulting from filler incorporation demonstrate that filler-modified ABS membranes have strong potential as alternative membranes for DMFC applications.